Nelson textbook of pediatrics - Vaughan, Victor C; Behrman, Richard E; McKay, R. James; Nelson, Waldo Emerson (W. B. Saunder, 1979)
Tap into all of the latest knowledge and expertise in your field ... in print and online! Both a user-friendly printed reference and a fully searchable web site, the e-dition of this classic text gives you two fast ways to find expert solutions to the clinical challenges that arise in your practice. Regular updates online ensure that you\'ll always have access to the most current information!Equips you with state-of-the-art, evidence-based guidance to help you offer your patients the best possible outcomes.Includes more than 750 outstanding illustrations that show you exactly what to look for and how to proceed.Uses highly structured full-color page layouts inside the printed book to make reference effortless.Offers rapid access to the answers you need via the fully searchable web site.Delivers regular updates online, overseen by the authors, to keep you continually apprised of important new clinical developments.Lets you download all of the book\'s illustrations for use in electronic presentations.Links references to the corresponding MEDLINE abstracts to simplify further research.Your purchase entitles you to access the web site until the next edition is published, or until the current edition is no longer offered for sale by Elsevier, whichever occurs first. If the next edition is published less than one year after your purchase, you will be entitled to online access for one year from your date of purchase. Elsevier reserves the right to offer a suitable replacement product (such as a downloadable or CD-ROM-based electronic version) should access to the web site be discontinued.
Keywords: Child; Child Development; Pediatrics; pediatrie; novorozenec; dítě; vývoj dítěte; neonatologie; Infant, Newborn; Psychology, Child; Neonatology; dětská psychologie